Erosional and depositional subglacial streamlining processes at Skálafellsjökull, Iceland: an analogue for a new bedform continuum model. (3rd April 2018) - Hart, Jane K.; Clayton, Alexander I.; Martinez, Kirk; Robson, Benjamin A.
Abstract: We combine the use of the unique Glacsweb in situ embedded sensors, surface velocity measurements (from dGPS and remote sensing), and UAV and field photographic surveys, to understand the subglacial processes responsible for the formation of a series of subglacial bedforms composed of both till and bedrock. There is till deformation throughout the year, with spatial and temporal variations. We estimate the ice velocity associated with the formation of a range of subglacial bedforms (9.2–31 m a −1 ) and the erosion rate on the bedrock flutes (2.13 mm a −1 ). We show that there is simultaneous deposition and erosion (either at the base of till or directly by ice) which generates flutes, large flutes and drumlins (rather than just depositional processes required by the instability theory). The flutes form behind obstacles associated with mobile till. Where a stationary obstacle is below a threshold height (which at this site is 1.56 m), either till tails will form behind the obstacle or a large flute will develop. Where a stationary obstacle is above a threshold height, then drumlins may form. Using these results as an analogue for larger bedforms, we discuss the bedform continuum in relation to elongation ratio, height, glacier velocity and bed mobility. These bedforms form associated with an overall net erosional regime, and once bedforms are produced, they may become fixed due to the presence of stationary obstacles, and so the resultant bedforms result from the most recent, as well as legacy, processes as they evolve over time.